2011
DOI: 10.1111/j.1467-9299.2011.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

The State and the Threat of Cascading Failure Across Critical Infrastructures: The Implications of Empirical Evidence From Media Incident Reports

Abstract: The threat of cascading failures across critical infrastructures has been identified as a key challenge for governments. Cascading failure is seen as potentially catastrophic, extremely difficult to predict and increasingly likely to happen. Infrastructures are largely privately operated and private actors are thought to under-invest in mitigating this threat. Consequently, experts have demanded a more dominant role for government, including the use of regulation. Empirical evidence on cascading failure is, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 24 publications
2
79
0
Order By: Relevance
“…A more recent empirical study [11], shows that events can been classified as cascade initiating (i.e., an event that causes an event in another CI), cascade resulting (i.e., an event that results from an event in another CI), and independent (i.e., an event that is neither a cascade initiating nor a cascade resulting event). The empirical findings indicate that:…”
Section: Dependencies and Interdependenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent empirical study [11], shows that events can been classified as cascade initiating (i.e., an event that causes an event in another CI), cascade resulting (i.e., an event that results from an event in another CI), and independent (i.e., an event that is neither a cascade initiating nor a cascade resulting event). The empirical findings indicate that:…”
Section: Dependencies and Interdependenciesmentioning
confidence: 99%
“…Using a dataset on CI disruption incidents, empirical analysis [10,11] showed that interdependencies-mutual dependencies-seldomly occur. Newer analysis shows that the only interdependencies that are mentioned in press reports occur at a lower, component or subsystem, level of abstraction.…”
Section: Dependencies and Interdependenciesmentioning
confidence: 99%
“…Regardless of the underlying methodology, risk assessors would have a priori knowledge or intuition about the most important nodes in cascading failure scenarios. For example, empirical results show that energy nodes and information and communications nodes are the most common cascade initiators [15].…”
Section: Centrality Measures For Dependency Graphsmentioning
confidence: 99%
“…In the case of a dependency risk graph, nodes with high closeness tend to be part of many dependency chains; sometimes these nodes may even initiate dependency chains. Since cascading effects tend to affect relatively short chains (empirical evidence indicates that cascades rarely propagate deeply [15]), nodes with high closeness centrality would have larger effects on the overall risk of dependency chains than nodes with low closeness centrality. To formalize this idea, consider Equation (1) that computes the cumulative risk of a dependency chain: the closer a node is to the initiator of a cascading event, the greater the effect it has on the cumulative dependency risk.…”
Section: Centrality Measures For Dependency Graphsmentioning
confidence: 99%
“…However, threats in the quality of water distribution have also been identified due to loss of pressurised water, aging infrastructure, as well as vulnerabilities in interdependent infrastructure [3,4,5]. While case studies provide a means of disseminating nuances to the broader research and practitioner communities,it would be useful to share such insights using a format suitable for evaluating new innovation by researchers, or products and services by practitioners.…”
Section: Introductionmentioning
confidence: 99%